2015
DOI: 10.2298/hemind140701002z
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl polyglucoside-stabilized emulsion as a prospective vehicle for Usnea barbata CO2-supercritical extract: Assessing stability, safety and efficiency of a topical formulation

Abstract: Antimicrobial activity of Usnea barbata especially against bacteria involved in pathogenesis of various skin conditions has been well documented in literature. Nevertheless, there are no papers dealing with formulation of its isolates into topical preparations for treatment of skin infections. In present study, alkyl polyglucoside (APG)-based vehicle was developed as carrier of U. barbata CO 2 -supercritical extract (U-SE) that demonstrated the best antimicrobial potential in preliminary screening. For compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Similar results were reported in the study of Weckesser et al (2007) that screened 9 lichen extracts and isolated compounds against bacterial and fungal species with dermatological relevance, singling out an extract of U. barbata prepared using supercritical CO 2 as the most active one, especially against and Malassezia furfur. Similarly, Zugic et al (2015) reported supercritical CO 2 extract of U. barbata to have the strongest antimicrobial effect against G(+) bacteria compared to the extracts of this lichen prepared using conventional techniques. Relatively strong activity of U. ghattensis was observed in a study that investigated antimicrobial activity of this lichen against G(+) and G(-) human pathogenic bacterial species, whereby methanol extract was the only extract active against Streptococcus faecalis, ethanolic extract was more effective than acetone and methanol extract against Bacillus cereus and Pseudomonas aeruginosa, while acetone and methanol extract showed similar activity against Staphylococcus aureus (Srivastava et al, 2013).…”
Section: Antimicrobial Activitymentioning
confidence: 86%
See 2 more Smart Citations
“…Similar results were reported in the study of Weckesser et al (2007) that screened 9 lichen extracts and isolated compounds against bacterial and fungal species with dermatological relevance, singling out an extract of U. barbata prepared using supercritical CO 2 as the most active one, especially against and Malassezia furfur. Similarly, Zugic et al (2015) reported supercritical CO 2 extract of U. barbata to have the strongest antimicrobial effect against G(+) bacteria compared to the extracts of this lichen prepared using conventional techniques. Relatively strong activity of U. ghattensis was observed in a study that investigated antimicrobial activity of this lichen against G(+) and G(-) human pathogenic bacterial species, whereby methanol extract was the only extract active against Streptococcus faecalis, ethanolic extract was more effective than acetone and methanol extract against Bacillus cereus and Pseudomonas aeruginosa, while acetone and methanol extract showed similar activity against Staphylococcus aureus (Srivastava et al, 2013).…”
Section: Antimicrobial Activitymentioning
confidence: 86%
“…Antimicrobial activity of usnic acid was investigated in many scientific papers and most of them described screening of this dibenzofuran derivative against various bacteria, fungi, and parasites. Its antibacterial activity has been documented for many G (+) bacteria (Gollapudi et al, 1994;Ivanova et al, 2010;Manojlović et al, 2012;Ranković et al, 2012;Schmeda-Hirschmann et al, 2008;Sultana and Afolayan, 2011;Weckesser et al, 2007;Zugic et al, 2015). In a recently published study dealing with the evaluation of usnic acid antibacterial activity against methicillin-resistant S. aureus (MRSA), it was found that the mechanism of antistaphylococcal activity was based on its capability to trigger the bacterial cell membrane destruction (Gupta et al, 2012).…”
Section: Usnic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of biological activities of lichens and their secondary metabolites with potential medical relevance over the past decades have singled out usnic acid as one of the most prominent lichen substances. Usnic acid was the subject of a vast majority of studies, including the ones discussing this substance as an isolated compound [1] or as a part of the usnic acid-containing lichens extracts [2][3][4][5], as well as investigations dealing with chemical derivatives of usnic acid [6]. As the stated studies suggested, usnic acid or its derivatives possess various biological activities, such as antimicrobial against various bacteria, fungi and parasites, as well as antioxidant, cytotoxic (antitumor), neuroprotective, gastroprotective, cardioprotective, cytoprotective, immunostimulatory, anti-inflammatory and wound healing properties [1].…”
Section: Introductionmentioning
confidence: 99%